Effects of Pranoprofen on Aqueous Humor Monocyte Chemoattractant Protein-1 Level and Pain Relief During Second-Eye Cataract Surgery - Zhang, Yinglei; Du, Yu; Jiang, Yongxiang; Zhu, Xiangjia; Lu, Yi (Frontiers in Pharmacology, 2018)
The aim of our present study is to evaluate the efficacy of pranoprofen eye drops as pain relief during sequential second-eye cataract surgery and to investigate the possible mechanism. Seventy-six patients scheduled for bilateral sequential cataract surgery were randomly assigned to two groups: (1) treatment group (administered pranoprofen eye drops), or (2) control group (administered artificial tears). Preoperative anxiety and intraoperative pain were assessed. Monocyte chemoattractant protein 1 (MCP-1) in the aqueous humor was measured with a suspension cytokine array. An extracapsular lens extraction model was established in the Wistar rat and the MCP-1 concentrations were measured with an enzyme-linked immunosorbent assay. We found that in the control group, the pain scores were significantly higher during second-eye surgery than during first-eye surgery (both scores P < 0.001). In the treatment group, there was no significant difference in the pain scores during first-eye and second-eye surgery (both scores P > 0.1). The pain during second-eye surgery was significantly lower in the treatment group than in the control group (both scores P < 0.01). And in the 1-week and 6-week interval subgroups, the pain scores during second-eye surgery were significantly lower in the treatment group than the control group (P = 0.047 and P = 0.035, respectively). While the second-eye MCP-1 level was significantly lower after a 1-week interval in the treatment group than in the control group (P = 0.012), but did not differ significantly after a 6-week interval (P > 0.1). A parallel trend in the MCP-1 concentration was detected in the rat model. In conclusion, the preoperative administration of pranoprofen eye drops reduced the perceived pain during second-eye cataract surgery, especially when performed after 1-week and 6-week intervals between the first-eye and second-eye surgery. MCP-1, a pain-related cytokine, was associated with the pain-relief mechanism of pranoprofen when second-eye surgery was performed 1 week after second-eye surgery.